Experimental Study on Basic Mechanical Properties of Steel Fiber-Reinforced Siliceous Wet Shotcrete - Xu Yan; Li-min Liu; Jin-peng Zhang; Yan-hui Li; He Wang (Advances in Materials Science and Engineering)
In order to solve the problem of low strength and easy cracking of shotcrete in permanent support of tunnel single shell lining, the effects of steel fiber-reinforced siliceous on mechanical properties of wet shotcrete were investigated by the tests of compressive strength, splitting tensile strength, flexural strength, shear strength, and bending toughness. The strength and the cracking resistance mechanism of steel fiber-reinforced siliceous wet shotcrete were analyzed by the bending toughness evaluation method. The results show that (1) the steel fiber-reinforced siliceous can improve splitting tensile, flexural, and shear capacity of the shotcrete, and the maximum growth rates were 77.42%, 72.73%, and 98.31%. The steel fiber plays a major role, and silica fume plays a subsidiarity role. (2) The effect of different types and contents of steel fibers on the compressive strength of wet shotcrete are not obvious. (3) The strengthening effect of shear undaform steel fiber on concrete is obviously better than that of shear flat steel fiber. (4) The flexural toughness of wet shotcrete with the silica content of 10% and the shear steel fiber of 60 kg/m3 is the best.